Hubungan Kompetensi Kognitif Rapid Health Assessment dengan Tingkat Kesiapsiagaan Bencana Mahasiswa Kesehatan - Muhammad Falih Marwan; Zukhriana K Yusuf; Serly Daud; Abdi Dzul Ikram Hasanuddin; Sri Manovita Pateda (Jurnal Ners, 2026)
Escalating disasters in Indonesia (3,472 events in 2024) demand Rapid Health Assessment (RHA) competency among health students, yet curriculum integration remains inadequate. This study aimed to analyze the correlation between cognitive RHA competency and disaster preparedness. An observational analytic cross-sectional study involved 310 medical, nursing, and midwifery students at Universitas Negeri Gorontalo using Proportional Stratified Random Sampling. Instruments comprised Guttman scale questionnaires (RHA knowledge) and Likert scale (preparedness), analyzed via Spearman's Rho test (α=0.05) using SPSS. Results revealed 61.1% respondents achieved "Good" RHA knowledge category with significant correlation (p=0.004). The study concludes RHA competency positively contributes to disaster preparedness through implicit knowledge, recommending interprofessional simulation for curriculum transformation.